2008
DOI: 10.1186/1477-7517-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the need for safe storage of Methadone at home is not improved by the use of protocols on recording information giving

Abstract: Background: Methadone is a synthetic, narcotic analgesic used in the treatment of drug misuse. Tragedies involving children being poisoned by the accidental ingestion of methadone are no longer a rare occurrence. Following an audit of the effectiveness of the provision and recall of information to patients attending an NHS Methadone Clinic a protocol was introduced to ensure that staff documented the provision of such information and patients gave a written confirmation that they had received the information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The risk to children posed by methadone in the UK has recently been highlighted in an analysis of 20 serious case reviews involving young children exposed to opioid substitution therapy medications 18. Previous UK surveys have demonstrated that many patients receiving methadone were not aware of its dangers to children, do not recall being given safe storage advice or do not keep their methadone in a safe locked location,19 20 although somewhat better results were obtained in an Australian study 21. It is therefore vital that prescribers ask patients repeatedly about the presence of children in their homes and adapt advice and/or practice accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The risk to children posed by methadone in the UK has recently been highlighted in an analysis of 20 serious case reviews involving young children exposed to opioid substitution therapy medications 18. Previous UK surveys have demonstrated that many patients receiving methadone were not aware of its dangers to children, do not recall being given safe storage advice or do not keep their methadone in a safe locked location,19 20 although somewhat better results were obtained in an Australian study 21. It is therefore vital that prescribers ask patients repeatedly about the presence of children in their homes and adapt advice and/or practice accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of methadone treatment have been marred by a number of accidental fatal methadone intoxication cases in children (Binchy, Molyneux, & Manning, 1994;Mullin, McAuley, Watts, Crome, & Bloor, 2008), either by unsafe storage procedures (Binchy et al, 1994;Calman, Finsh, Powis, & Strang, 1996) or by parental administration of the drug to an infant for sedation (Couper, Chopra, & Pierre-Louis, 2005;Li, Levine, & Smialek, 2000). Education programmes and public health campaigns may be effective in promoting the dangers of drug intoxication.…”
mentioning
confidence: 96%
“…The questionnaire was developed with reference to previous studies. [5,6] Draft versions of the questionnaire were assessed by members of the User Involvement Group of the Scottish Drugs Forum. The questionnaire was also piloted on five practice patients.…”
Section: Methodsmentioning
confidence: 99%
“…Definitions of safe storage were based on good practice guidelines and on previous studies. [5,6] Storage of medication was classified as 'acceptable' if medication was out of sight and out of reach of children (for example in a high cupboard or wardrobe), and 'optimal' if it was also kept in a secure container (such as a locked cupboard or child-resistant box).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation